2017
DOI: 10.3389/fpsyt.2017.00081
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results from the Empowering a Multimodal Pathway Toward Healthy Youth Program, a Multimodal School-Based Approach, Show Marked Reductions in Suicidality, Depression, and Anxiety in 6,227 Students in Grades 6–12 (Aged 11–18)

Abstract: Here, we report on findings from a 15-month follow-up of a school-based program called Empowering a Multimodal Pathway Toward Healthy Youth (EMPATHY). This was primarily intended to reduce suicidal thinking in pre-teens, adolescents, and youth students aged 11–18 in middle schools (Grades 6–8) and high SCHOOLS (Grades 9–12). It also aimed to reduce depression and anxiety. The EMPATHY multimodal program consisted of repeated data collection, identification of a high-risk group, a rapid intervention for this hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…The Fort McMurray survey also included a demographics questionnaire, which was somewhat different from the Red Deer one. Full details of the EMPATHY project are available [24, 25]. In this paper, we focus on the six questionnaires that were used in both the communities of Fort McMurray and Red Deer, using Red Deer as a control population.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fort McMurray survey also included a demographics questionnaire, which was somewhat different from the Red Deer one. Full details of the EMPATHY project are available [24, 25]. In this paper, we focus on the six questionnaires that were used in both the communities of Fort McMurray and Red Deer, using Red Deer as a control population.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we focus on the six questionnaires that were used in both the communities of Fort McMurray and Red Deer, using Red Deer as a control population. Ethics considerations for data collection in the Red Deer EMPATHY project have been described in detail previously [24, 25] but were similar to those for the Fort McMurray data collection. The EMPATHY program itself was approved by the Health Research Ethics Committee of the University of Alberta on December 5th, 2013, ethics protocol number Pro00041063.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final sample included 26 studies ( Table 1 ) [ 34 - 59 ]. Although various professional disciplines were represented (ie, social work, medicine, public health), over half (n=16) of the first authors held a doctoral degree in psychology.…”
Section: Resultsmentioning
confidence: 99%
“…Our respondents may have been concerned about confidentiality and stigma, which can prevent young people from seeking help. Two studies have used a school-based education program, including Internet-based cognitive behavioral therapy, to improve suicidality in young people: one study found a significant effect, but the other found no effect [34,35]. Such trials may be an effective way of helping young people access help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%